Communication Between Parents and Young People on Sexual and Reproductive Health Issues and Its Associated Factors in Holeta and Bako Towns, Oromia, West Ethiopia: A Cross‐Sectional Study - Tsegaye Benti Muse; Hunduma Dinsa Ayeno; Mulugeta Mekuria Mengistu; Yohannes Bacha Gemechu; Seifadin Ahmed Shallo; Elias Teferi Bala (Health Science Reports)
ABSTRACT Background Despite the importance of sexual and reproductive health (SRH) communication in increasing accessibility to SRH care, its prevalence is not significant. In Ethiopia, communication between parents and young people is restricted, similar to the situation in other developing nations, as demonstrated by various studies. Aim To assess communication between parents and young people on SRH issues and their associated factors in Holeta and Bako Towns, Oromia, West Ethiopia, 2020. Methods A community‐based cross‐sectional study was conducted among 558 study subjects selected using a simple random sampling technique. Data were collected using interviewer‐administered structured questionnaires, entered into Epi Data version 4.6, and exported to SPSS version 25 for analysis. Descriptive statistics were conducted for common variables. Binary and multiple logistic regression analyses were performed to identify factors associated with SRH communication using a 95% confidence interval and a p‐value less than 0.05. Results This study revealed that 38.5% of young people had ever discussed SRH topics with their parents. Factors associated with this communication included being male (AOR = 2.21, 95% CI: [1.42, 3.44]), having a family size of less than six (AOR = 1.73, 95% CI: [1.14, 2.61]), being aged 20–24 years (AOR = 1.86, 95% CI: [1.06, 3.25]), having ever heard about SRH (AOR = 2.31, 95% CI: [1.45, 3.67]), having a positive attitude (AOR = 2.26, 95% CI: [1.48, 3.45]), having knowledge about SRH (AOR = 3.48, 95% CI: [2.20, 5.49]), and having a higher family monthly income (AOR = 3.09, 95% CI: [1.58, 6.04). Conclusion Parental engagement in SRH discussions with young people is low and inconsistent, varying across different age groups. This lack of communication may be influenced by cultural barriers, such as feelings of embarrassment. Therefore, there is a crucial need to address the limited involvement of parents in programs aimed at providing SRH services to young people.